PENANGANAN PERKARA KORUPSI BERKUALITAS OLEH KEJAKSAAN SEBAGAI BAGIAN DARI UPAYA PENCEGAHAN - Budi Triono (2021)
Handling quality corruption cases by the Prosecutor's Office of the Republic of Indonesia as one of the law enforcement institutions that has the main task and function in law enforcement, which is implemented by the Prosecutor's Office in terms of eradicating and preventing quality corruption crimes based on legal politics on the basis of the Letter of the Deputy Attorney General for Special Crimes Number: B-845/F/Fjp/05/2018 dated May 4, 2018 regarding the Technical Guidelines for the Handling of Qualified Special Crime Cases by the Indonesian Attorney General's Office and is associated with the Handling of Corruption Crime Cases that occurred PT. Asuransi Jiwasraya that in the application of the Circular is intended to achieve quality case handling and prevent irregularities in the handling of special criminal cases. The contents are related to the criteria for law enforcement through preventive and repressive efforts and without selective discrimination, as well as several criteria for eradicating corruption by building a corruption-free zone through strengthening the awareness of individuals and groups of state institutions, eradicating corruption to the root of the problem and looking for the factors causing it, and carry out the handling of corruption cases in accordance with procedures. In its implementation, it has been integrated with national development planning which focuses on taking action against 10 corruption-prone areas where this is a parameter (benchmark) of corruption cases which are categorized as big fish. In addition, the handling of corruption cases is carried out by the Prosecutor's Office of corruption cases in accordance with the technical pattern of handling special criminal cases, namely the investigation, investigation, pre-prosecution, prosecution, trial, ordinary legal remedies, implementation of court decisions (execution) and until extraordinary legal efforts and examinations which are an effort to realize quality handling of general crimes, especially in eradicating corruption.